Pengaruh Sistem Informasi Manajemen Akademik (SIMAK) Terhadap Efektivitas Pelayanan Administrasi Perguruan Tinggi - Nurilahi; Andi Putri Rahayu Maharani; Hari Yeni (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
Village administrative services play an important role in improving the quality of life for the community. The implementation of the Village Administration Information System (SIPAD) is expected to accelerate administrative processes, improve data accuracy, and provide easier access to services for residents. This study aims to analyze the effect of SIPAD implementation on community satisfaction in Tabulahan Village. A quantitative survey method was employed, with data collected from 120 respondents using questionnaires and analyzed through simple linear regression. The results indicate that the implementation of SIPAD has a positive and significant effect on community satisfaction, with a coefficient of determination (R²) of 0.68, showing that 68% of the variation in community satisfaction can be explained by SIPAD implementation. The discussion emphasizes that SIPAD facilitates village officials in managing administration, speeds up service delivery, and enhances transparency, leading to higher satisfaction among residents. In conclusion, SIPAD plays a crucial role in increasing community satisfaction, and village authorities need to continue optimizing the system to maintain efficient, fast, and responsive public services.